2019
DOI: 10.1002/cctc.201900298
|View full text |Cite
|
Sign up to set email alerts
|

Mordenite Nanorods Prepared by an Inexpensive Pyrrolidine‐based Mesoporogen for Alkane Hydroisomerization

Abstract: We report the synthesis of hierarchical mordenite zeolite nanorods in one step using inexpensive mono‐quaternary ammonium N‐cetyl‐N‐methylpyrrolidinium (C16NMP) as mesoporogen to the synthesis gel. The presence of a small amount of C16NMP results in the formation of 0.6–1 μm rods‐like crystals oriented along the c‐axis with a high mesoporous volume (0.12 cm3 g−1) and external surface area (∼90 m2 g−1) compared to bulk mordenite. Acidity characterization shows that the presence of C16NMP during mordenite format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
1
18
0
1
Order By: Relevance
“…The starting material is a MOR zeolite prepared with a charged C 16 NMP (Ncetyl-N-methylpyrrolidinium cation) as the SDA. 42 The use of this amphiphilic SDA results in a hierarchical pore structure with potential benefits to catalysis. We demonstrated that, after loading of Pd nanoparticles, this zeolite shows improved performance in bifunctional n-hexadecane hydroconversion compared to bulk MOR zeolite because of a reduced amount of acid sites in the main 12-membered ring channels as well as the presence of mesopores.…”
Section: Optimization Nh 4 F Treatment For the Mor Zeolitementioning
confidence: 99%
See 1 more Smart Citation
“…The starting material is a MOR zeolite prepared with a charged C 16 NMP (Ncetyl-N-methylpyrrolidinium cation) as the SDA. 42 The use of this amphiphilic SDA results in a hierarchical pore structure with potential benefits to catalysis. We demonstrated that, after loading of Pd nanoparticles, this zeolite shows improved performance in bifunctional n-hexadecane hydroconversion compared to bulk MOR zeolite because of a reduced amount of acid sites in the main 12-membered ring channels as well as the presence of mesopores.…”
Section: Optimization Nh 4 F Treatment For the Mor Zeolitementioning
confidence: 99%
“…A conventional MOR sample denoted as MOR-H (hierarchical) was synthesized according to the procedure described in our previous report. 42 The sample constituted a highly crystalline MOR zeolite with a Si/Al ratio of 9 (Fig. 10).…”
Section: Optimization Nh 4 F Treatment For the Mor Zeolitementioning
confidence: 99%
“…An observed lattice distance of 1.33 nm is attributed to the [110] plane (Figure 13c, insert) and points to nanorods oriented parallel to the c -axis. 25,62,63 As discussed in our previous work, 25 the hydrophilic head group of the SDA molecule is likely located in the 8 MR side-pockets or at the interface between the 8MR and 12MR channels, while the hydrophobic tail is blocking crystal growth in the a - and b -directions.…”
Section: Results and Discussionmentioning
confidence: 84%
“…The samples exhibited similar catalytic behavior, namely, a low selectivity to cracking products up to n -hexadecane conversion of 80% (Figure 12c), explained by the relatively weak acidity 25 of the amorphous materials (Table S4). The Pd/Com-ASA displayed a slightly “M-shaped” distribution of cracked product (Figure 12d), whereas the Pd/Al-LS sample showed a more symmetric distribution of cracked products at 50% conversion.…”
Section: Results and Discussionmentioning
confidence: 88%
“…This last decrease caused a better hydrocracking selectivity since 12-MR acid sites are otherwise involved in the conversion of alkene intermediates. [274] In contrast to previous template-assisted methods, another synthesis strategy is possible, which falls under the concept of kinetic regulation. Herein, the hierarchical zeolite is synthesized without using a template, but by controlling the zeolite crystallization process so that a balance between nucleation and crystal growth is achieved.…”
Section: Nanozeolites and Their Assemblymentioning
confidence: 99%